2019
DOI: 10.1021/acs.joc.9b02522
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Isonitrile/Tetrazine Chemistry for Accelerated Deprotection and Formation of Stable Conjugates

Abstract: The isocyano group is a valuable functionality for bioorthogonal reactions because it rapidly reacts with tetrazines to either form stable conjugates or release payloads from 3-isocyanopropyl groups. Here we provide mechanistic insights into the dissociative steps that follow the initial cycloaddition and analyze how structural modifications affect these processes. Three main outcomes of this study have important implications for designing such groups for bioorthogonal applications. First, anion-stabilizing su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 41 publications
0
26
0
Order By: Relevance
“…However, we recently showed that even simple primary isonitriles can form stable linkages with tetrazines that have bulky substituents. 36 The adduct of 3,6bis-tert-butyl-1,2,4,5-tetrazine and n-butyl isocyanide was stable in D 2 O/DMSO-d 6 (1:1), with a gradual hydrolysis of 18% in 72 hours. 36 Based on this result, it is now possible to exploit the structural compactness of the isocyano group for labeling applications, opening new opportunities in chemical biology.…”
Section: The Isocyano Group: a Structurally Compact Group For Bioorthogonal Chemistrymentioning
confidence: 98%
See 1 more Smart Citation
“…However, we recently showed that even simple primary isonitriles can form stable linkages with tetrazines that have bulky substituents. 36 The adduct of 3,6bis-tert-butyl-1,2,4,5-tetrazine and n-butyl isocyanide was stable in D 2 O/DMSO-d 6 (1:1), with a gradual hydrolysis of 18% in 72 hours. 36 Based on this result, it is now possible to exploit the structural compactness of the isocyano group for labeling applications, opening new opportunities in chemical biology.…”
Section: The Isocyano Group: a Structurally Compact Group For Bioorthogonal Chemistrymentioning
confidence: 98%
“…36 The adduct of 3,6bis-tert-butyl-1,2,4,5-tetrazine and n-butyl isocyanide was stable in D 2 O/DMSO-d 6 (1:1), with a gradual hydrolysis of 18% in 72 hours. 36 Based on this result, it is now possible to exploit the structural compactness of the isocyano group for labeling applications, opening new opportunities in chemical biology. In another bioorthogonal reaction, simple isonitriles react with chlorooximes under physiological conditions forming -hydroximino amide linkages (Scheme 2).…”
Section: The Isocyano Group: a Structurally Compact Group For Bioorthogonal Chemistrymentioning
confidence: 98%
“…Meanwhile, Franzini’s group thoroughly explored the structure-activity relationship of the reaction between isocyanides and tetrazines ( Table 1 ), and found that tetrazines with bulky substituents could form stable adducts with primary isocyanides, thus obviating the need for engineering the isocyanide moiety (e.g., tertiary isocyanides) ( Tu et al, 2019 ; Xu et al, 2019 ). What’s more interesting is that stable asymmetric tetrazines with bulky and electron-withdrawing substituents ( Tz-4 ) can react with isocyanides rapidly under high-water conditions ( Table 1 , Entries 12–13).…”
Section: Strategy 1: Isocyanide As a Bioorthogonal Handlementioning
confidence: 99%
“…However, toxic acrolein as a by-product, may impose restrictions on in vivo applications. Further mechanistic study suggests the elimination reaction is hydrolysis-independent and may avoid the generation of acrolein [93].…”
Section: Tetrazine-triggered Cleavage From Isonitrilementioning
confidence: 99%